The Influence of Siblings on Young Children’s Understanding of Fluid Intake - Williamson Josh; Howells Kristy (International Journal of Nutrition, 2021)
Background Children need to drink enough water (1.1-1.3 litres) throughout the day to stay hydrated and for health benefits1. Wellbeing and cognitive function benefits have been identified for children who are hydrated2. Yet there is a dearth of research focusing specifically on children’s perceptions of their own fluid intake levels and who helps support them in ensuring they are drinking enough water, this is a novel area to investigate. Previous research3 identified that 44.2% of young children’s fluid intake were influenced the strongest by a family member. This paper will explore in further detail the influence of siblings on children’s fluid intake, in particular older versus younger siblings. Methods 130 children (67 girls and 63 boys, of which 45 had a younger sibling (s) and 85 having an elder sibling(s), from 4 primary schools in the South East of England, were questioned between January and April 2019 using an adapted version of Coppinger and Howells’ (2019)4 questionnaire, on their understanding of fluid intake, how much they perceived they drank and who supported them in prompting them to drink. Physical visual representations were used to aid question comprehension and to ensure the questions were appropriate for young children. The data was analysed using SPSS 24.0 using MANOVAs (P < 0.05) to consider statistical variance in gender and older sibling status. Results The most significant results were linked to elder siblings influence younger siblings in drinking too little fluids within a school day (F=0.530, p<0.05), whilst those without an elder sibling, thought they drank beyond the daily recommended guidelines and reported they drank over 2 litres. This illustrates that children misunderstand fluid intake recommendations regardless of whether they have an elder sibling or not. Children named adults, both parents and teachers as well as elder siblings as the key influencers of them drinking (F=3.67, p<0.05) and the data indicated that girls were more influenced by siblings than boys, whilst twins were not influenced by each other. Conclusion It is concluded that siblings do have an influence on the consumption of water, as siblings act as role models and other siblings follow their habits, therefore the whole family unit is important to ensure that the right fluid intake is consumed. It is recommended that further education, curriculum and community development is needed to continue to support young children’s knowledge and understanding of fluid intake.
Keywords: Fluid intake